Chitosan for suppression of fusarium wilt and plant growth promotion of brinjal - S. Chaterjee; Rayhanur Jannat; M. M. Hossain; M. R. Amin; M. T. Rubayet (Future Science, 2021)
Chitosan is a biodegradable natural compound that has a great potentiality in agriculture for controlling plant diseases. An attempt was made to control Fusarium wilt caused by Fusarium oxysporum f. sp. melongenae under inoculated field condition and increase the growth and yield of brinjal by chitosan. Before setting the experiments in the field, preliminary laboratory experiments were carried out to select virulent isolate and effective dose of chitosan against the mycelial growth of the selected pathogen. F. oxysporum f. sp. melongenae isolate F-1 was found to be the most virulent on brinjal in pathogenicity test. Chitosan @ 1.0% concentration was appeared to be the highest inhibitory to the test pathogen at in vitro condition. Additionally, seed treatment with 1.0% chitosan for 12 hrs resulted in the highest increased in germination and seedling growth of brinjal. The field experiment was conducted following Randomized Complete Block Design (RCBD) with four treatments. No treatment was given in T1, the pathogen was inoculated in T2 and seed treatment and soil amendment with 1.0% chitosan was done in T3 and T4, respectively, in test pathogen inoculated condition. Application of 1.0% chitosan as a seed treatment (T3) or soil amendment (T4) significantly reduced pre- and post-emergence seedling mortality, incidence and severity of Fusarium wilt as well as enhanced germination percentage, plant growth and yield of brinjal. On the contrary, pre-emergence and post-emergence seedling mortality, disease incidence and severity of Fusarium wilt were highest in treatment T2 where the soil was inoculated with pathogen without chitosan. Therefore, chitosan could be used against this vascular disease as an alternative to inorganic fungicides and augment yield.